PENGARUH ORGANIZATIONAL JUSTICE TERHADAP ORGANIZATIONAL COMMITMENT PADA KARYAWAN PT X - Anggoro, Wahyu; Ardiwinata, Maya Rosmayati; Yanuarti, Nurul (Universitas Muhammadiyah Jember, 2020)
PT X aims its vision to become a World Class Life Science Company with Global Competitiveness. In order to support that vision, PT X needs its employees to be committed to contribute in achieving said vision. This research aims to investigate the effect of Organizational Justice to Organizational Commitment among the employees of PT X using linear regression statistical analysis. The research was done to 550 employees on the level of Heads of Department all the way to the Operators using supervised self-report questionnaires. Data collection was done by deploying Organizational Justice questionnaire, developed from the Justice Questionnaire by Colquitt et al., and Organizational Commitment questionnaire based on the questionnaire by Allen & Meyer. Research result indicates significant effect of Organizational Justice towards Affective (R=0,436, p<0,001), Continuance (R=0,087, p<0,001), and Normative (R=0,411, p<0,001) Commitment.